The risk of perchlorate and iodine on the incidence of thyroid tumors and nodular goiter: a case-control study in southeastern China - Huirong Wang; Yousheng Jiang; Jiayi Song; Huiwen Liang; Yuan Liu; Jiewu Huang; Pengliang Yin; Dongting Wu; Hang Zhang; Xinjie Liu; Dongxian Zhou; Wei Wei; et al. (BMC, 2022)
Highlights Patients with thyroid tumor have higher perchlorate exposure than control. Perchlorate can increase the risk of papillary thyroid carcinoma. Perchlorate can disturb the homeostasis of thyroid function. Perchlorate was positively correlated with thyroglobulin antibody.